Espaço regional e ensino superior em Vitória da Conquista Bahia - Gusmão, Adriana David Ferreira (2009)
The presented work was based on the concepts of region, geographical networks and that of space fixtures and flows, by taking them as parameters to discuss the relevance of higher education and its contributions for the production of space in Southwestern Bahia, the studies being focused on the provision of this teaching modality in Vitória da Conquista and its repercussion in that region. The analysis highlighted the process of organizing fixtures and flows and the buildup of geographical networks promoted by service provision in higher education in the cities of Vitória da Conquista, Barra do Choça, Poções, Jequié, Itambé and Itapetinga. The conceptual study provided the basis for the theoretical referential which supported the research and enabled the structuring of the fieldwork which was carried out. A brief discussion about the process of implementation of higher education in the State of Bahia was necessary and, particularly, in Southeastern Bahia, as well as establishing the connection among the worked concepts as a means of explaining the possible interferences of the referred teaching modality in the process of space construction. The methodology used in the study followed quantitative and qualitative approaches. The first approach aimed at gathering information by means of questionnaires. The second approach, qualitative, aimed at applying interviews in order to broaden the research scope and the inclusion of new information and the correlation among data. After carrying out the investigation, it is concluded that the installation of higher education institutions in Vitória da Conquista, Bahia, has prompted the growth of real estate and services in that city, besides leading to the creation of a local network based on the demand and supply of presential graduation courses. Moreover, the aforementioned expansion has directly justified real estate speculation and investments in this sector although students are not directly benefited by the high rent costs and the like. In terms of socioeconomic reverberations in the municipalities participating in the network established by higher education in the Southwestern Region, one can say that the students recognize the improvement in the level of alumni s and graduates social and intellectual participation in their hometowns, mainly by those who choose to remain there after graduating.